IgG+ Extracellular Vesicles Measure Therapeutic Response in Advanced Pancreatic Cancer - Couto, Nuno (2022)
Funding Information: J.E. was supported by grant 765492 from H2020-MSCA-ITN-2017. J.M. was supported by “Fundação para a Ciência e a Tecnologia” (PD/BD/105866/2014). S.B. was supported by the EMBO Installation Grant 3921. This work was supported by the Champalimaud Foundation and grant LCF/PR/HR19/52160014 from “La Caixa” Foundation. M.O.’s research is partially supported by National Funds through FCT, Fundação para a Ciência e a Tecnologia, projects 343 UIDB/04674/2020 (CIMA) and H2020-MSCA-RISE-2020/101007950, with the title ”DecisionES—Decision Support for the Supply of Ecosystem Services under Global Change,” funded by the Marie Curie International Staff Exchange Scheme.